The effect of topical and systemic tranexamic acid on fracture healing in rats - ERCAN, FERİHA; KAYA, ÖZLEM TUĞÇE (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2020)
Objective: The aim of the present study was to determine the effect of topical and systemic tranexamic acid (TXA) on fracture healing in a rat surgical model. Methods: We created standard, right-sided, open, diaphyseal femoral fractures with intramedullary Kirschner wire fixation in 48 male rats and divided them into three groups: a topical TXA (10 mg/kg) group, a systemic TXA (10 mg/kg) group, and a control group. Fracture healing was evaluated radiographically and histologically after early (week 2) and late (week 4) postoperative sacrifice. Results: The radiological scores differed significantly among the all groups (p-0.001), as did the week 2 and 4 scores (p=0.003 and p=0.010, respectively). Radiologically, the topical TXA group exhibited better bone healing at both 2 (p=0.001) and 4 (p=0.007) weeks than the control group, and the systemic group showed better healing at both 2 (p=0.027) and 4 (p=0.023) weeks than the control TXA group. Moreover, bone healing was better in the group treated with topical rather than systemic TXA on radiological examinations performed at 2 (p=0.001) and 4 (p=0.007) weeks postoperatively (p=0.001 and p=0.007, respectively). Histologically, the groups differed significantly (p=0.001). The histological scores differed significantly among the all groups (p=0.001). At 2 weeks, the topical TXA group exhibited significantly better bone healing than the control group (p=0.001). Conclusion: Our results suggested that topical application of TXA in fracture patients may accelerate healing, whereas systemic administration may adversely affect healing.
Keywords: Tranexamic acid; Fracture healing; In vivo experiment; Fibrin; Hematoma; TOTAL HIP; KNEE ARTHROPLASTY; BLOOD-LOSS; BONE; TRANSFUSION; SURGERY; REPAIR; FIBRINOLYSIS; HEMATOMA